2012
DOI: 10.1590/s0101-31222012000300017
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do vigor de sementes de milho superdoce por meio da análise computadorizada de imagens de plântulas

Abstract: RESUMO -O presente trabalho foi conduzido com o objetivo de verificar a eficiência do sistema computadorizado de avaliação do vigor de sementes (SVIS ® ), em comparação com outros procedimentos disponíveis, em sementes de milho superdoce. Foram utilizadas sementes dos híbridos SWB 551 e SWB 585, cada uma representada por cinco lotes, conduzindo-se testes de germinação, envelhecimento acelerado (tradicional e com solução saturada de NaCl) e emergência de plântulas em campo. Para a determinação do vigor das seme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0
8

Year Published

2014
2014
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 10 publications
4
17
0
8
Order By: Relevance
“…For the vigor tests, accelerated aging showed the greatest similarity with the results of the SVIS ® evaluations in classifying lots with low vigor from those presenting high vigor. These results confirm those from soybean ) and super sweet corn seeds (ALVARENGA et al, 2012). The literature reports a high efficiency for the accelerated aging test for identify vigor differences between common bean seed lots (ALIZAGA et al, 1990) and the results of the current experiment demonstrated the SVIS ® analysis as a reliable procedure for evaluating seed vigor in common bean.…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…For the vigor tests, accelerated aging showed the greatest similarity with the results of the SVIS ® evaluations in classifying lots with low vigor from those presenting high vigor. These results confirm those from soybean ) and super sweet corn seeds (ALVARENGA et al, 2012). The literature reports a high efficiency for the accelerated aging test for identify vigor differences between common bean seed lots (ALIZAGA et al, 1990) and the results of the current experiment demonstrated the SVIS ® analysis as a reliable procedure for evaluating seed vigor in common bean.…”
Section: Resultssupporting
confidence: 85%
“…This information is important because it permit reduce by 24h the time for evaluating the seed vigor of common bean using the SVIS ® . In melon and cucumber seeds, in contrast, more accurate and consistent results were observed in four-day-old compared to three-day-old seedlings (MARCOS FILHO et al, 2006;CHIQUITO et al, 2012). Otherwise, the SVIS ® evaluations in three-day-old seedlings of Crotalaria juncea were more sensitive for identifying differences in vigor between seed lots in comparison with the four-day-old seedlings (SILVA et al, 2012a).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations